Salvage Following Transoral Laser Microsurgery for Early Glottic Cancer in National Veteran Database. (23rd July 2021) - Voora, Rohith S.; Panuganti, Bharat; Flagg, Mitchell; Kumar, Abhishek; Qian, Alexander S.; Kotha, Nikhil V.; Qiao, Edmund M.; Weissbrod, Philip A.; Rose, Brent; Orosco, Ryan K.
Abstract : Objectives: Transoral laser microsurgery (TLM) is commonly utilized for early glottic cancer and offers favorable oncologic and functional outcomes. However, the survival implications of salvage therapy for recurrent or persistent disease have not been definitively characterized. Study Design: Retrospective, national database cohort study. Methods: Data were extracted from Veterans Health Affairs (VHA) Informatics and Computing Infrastructure (VINCI) concerning the TLM‐based management of T1–T2 glottic squamous cell carcinoma patients between 2000 and 2017. Patients were characterized as either requiring TLM‐only, or in cases of persistent or recurrent local disease, TLM plus change in treatment modality (radiotherapy, chemoradiotherapy, or open surgery). Predictors of overall survival (OS), cancer‐specific survival (CSS), and salvage‐free survival were evaluated via Cox and Fine‐Gray models. Results: About 553 patients (70.9% T1a, 13.4% T1b, 15.7% T2) were included, with a median follow‐up time of 74.5 months. The need for non‐TLM salvage increased along with more advanced disease (11.7% T1a, 29.7% T1b, 32.2% T2). Compared to patients with T1a disease, those with T1b and T2 tumors initially treated with TLM had a significantly higher probability of receiving non‐TLM salvage (T1b: HR 2.70, 95% CI: 1.61–4.54; T2: HR 3.02, 95% CI: 1.88–4.84). In a multivariable model, receipt of non‐TLM salvage was not a significant predictor of either OS (HR = 0.91, 95% CI: 0.62–1.33, P = .624) or CSS (HR 1.21 95% CI 0.51–2.86, P = .667). Conclusion: The majority of patients with early glottic cancer that are managed with TLM do not require additional salvage therapy. When non‐TLM salvage was required, there was no decrement in OS or CSS. Level of Evidence: 4 Laryngoscope, 131:2766–2772, 2021